PROSES MENGAJAR DALAM AL-QUR’AN (Studi Analisis tentang Allah SWT Sebagai Pendidik Hakiki dan penerapannya dalam pendidikan) - Hamdi Pranata (STAI Tuanku Tambusai, 2021)
Abstract:Teaching is an activity process that should be planned in such a way and follow certain procedural steps so that the implementation and objectives will be achieved with the expected results. If the Qur'an is studied in more depth, some basic principles of education will be found which are used as a source of inspiration to be developed in order to build quality education including about Allah SWT who carries out the teaching process. This study uses a qualitative method of literature review using content analysis techniques. The result is that, Allah swt is an essential Educator who teaches various things, not only teaching humans but also angels and the Jinn nation. In addition, the Qur'an also explains the nature of Allah as education and the methods and media that Allah SWT uses in carrying out the teaching process.